C‐Jun N‐terminal kinase in pancreatic tumor stroma augments tumor development in mice. Issue 11 (18th September 2017) - Sato, Takeshi; Shibata, Wataru; Hikiba, Yohko; Kaneta, Yoshihiro; Suzuki, Nobumi; Ihara, Sozaburo; Ishii, Yasuaki; Sue, Soichiro; Kameta, Eri; Sugimori, Makoto; Yamada, Hiroaki; Kaneko, Hiroaki; et al.
Abstract : Pancreatic ductal adenocarcinoma (PDAC) is a life‐threatening disease and there is an urgent need to develop improved therapeutic approaches. The role of c‐Jun N‐terminal kinase (JNK) in PDAC stroma is not well defined even though dense desmoplastic reactions are characteristic of PDAC histology. We aimed to explore the role of JNK in PDAC stroma in mice. We crossed Ptf1a Cre/+ ; Kras G12D/+ mice with JNK1 −/− mice to generate Ptf1a Cre/+ ;Kras G12D/+ ;JNK1 −/− (Kras;JNK1 −/− ) mice. Tumor weight was significantly lower in Kras;JNK1 −/− mice than in Kras;JNK1 +/− mice, whereas histopathological features were similar. We also transplanted a murine PDAC cell line (mPC) with intact JNK1 s.c. into WT and JNK1 −/− mice. Tumor diameters were significantly smaller in JNK1 −/− mice. Phosphorylated JNK (p‐JNK) was activated in α‐smooth muscle actin (SMA)‐positive cells in tumor stroma, and mPC‐conditioned medium activated p‐JNK in tumor‐associated fibroblasts (TAF) in vitro . Relative expression of Ccl20 was downregulated in stimulated TAF. Ccl20 is an important chemokine that promotes CD8 + T‐cell infiltration by recruitment of dendritic cells, and the number of CD8 + T cells was decreased in Kras;JNK1 +/− mice compared with Kras;JNK1 −/− mice. These results suggest that the cancer secretome decreases Ccl20 secretion from TAF by activation of JNK, and downregulation of Ccl20 secretion might be correlated with reduction of infiltrating CD8 + T cells. Therefore, we concluded that inhibition of activated JNK in pancreatic tumor stroma could be a potential therapeutic target to increase Ccl20 secretion from TAF and induce accumulation of CD8 + T cells, which would be expected to enhance antitumor immunity. Abstract : The pancreatic cancer secretome decreases Ccl20 secretion from tumor associated fibroblasts (TAFs) via JNK activation, and downregulation of Ccl20 secretion might be correlated with reduction of infiltrating CD8 positive T cells. Inhibition of activated JNK in pancreatic tumor stroma could be a potential therapeutic target to increase Ccl20 secretion from TAFs and induce accumulation of CD8 positive T cells, which would be expected to enhance antitumor immunity.